2020
DOI: 10.1093/mnras/staa1749
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO Survey: membership probabilities for stars in 32 open clusters from 3D kinematics

Abstract: The Gaia-ESO Survey (GES) observed many open clusters as part of its programme to spectroscopically characterize the various Milky Way populations. GES spectroscopy and Gaia astrometry from its second data release are used here to assign membership probabilities to targets towards 32 open clusters with ages from 1 to 3800 Myr, based on maximum likelihood modelling of the 3D kinematics of the cluster and field populations. From a parent catalogue of 14 398 individual targets, 5032 stars with uniformly determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 79 publications
2
25
0
Order By: Relevance
“…It provides stellar parameters, metallicity, and elemental abundances, radial velocities, and additional products, such as gravity index, chromospheric activity tracers, mass accretion rate diagnostics, and veiling. Several works in recent years have been devoted to the study of open clusters observed by the GES, among many we recall the latest ones: Bertelli Motta et al [76], Magrini et al [77,78,79], Prisinzano et al [80], Hatzidimitriou et al [81], Casali et al [82,83], Baratella et al [84], Randich et al [85], Jackson et al [86], Bonito et al [87], Gutiérrez Albarrán et al [88], Semenova et al [89], Binks et al [90]. In the following sections, we adopt the average abundances from IDR6 for the member stars of 57 clusters with ages ≥ 120 Myr published in Magrini et al [79].…”
Section: Gaia-esomentioning
confidence: 99%
“…It provides stellar parameters, metallicity, and elemental abundances, radial velocities, and additional products, such as gravity index, chromospheric activity tracers, mass accretion rate diagnostics, and veiling. Several works in recent years have been devoted to the study of open clusters observed by the GES, among many we recall the latest ones: Bertelli Motta et al [76], Magrini et al [77,78,79], Prisinzano et al [80], Hatzidimitriou et al [81], Casali et al [82,83], Baratella et al [84], Randich et al [85], Jackson et al [86], Bonito et al [87], Gutiérrez Albarrán et al [88], Semenova et al [89], Binks et al [90]. In the following sections, we adopt the average abundances from IDR6 for the member stars of 57 clusters with ages ≥ 120 Myr published in Magrini et al [79].…”
Section: Gaia-esomentioning
confidence: 99%
“…with the lower(upper) limits corresponding to the case σ = 1(3) km s −1 , i.e. the typical value of velocity dispersion for MW young and open clusters (Soubiran et al 2018;Kuhn et al 2019;Jackson et al 2020), and to configuration NSSTBH(BHSTNS).…”
Section: Dynamical Formation Of Gw190814 and Gw190426 152155mentioning
confidence: 99%
“…Col. 8-9: individual merger rate for BHSTNS configuration and different metallicities. 1(Piskunov et al 2007;Soubiran et al 2018;Jackson et al 2020). 2 (Harris 2010).…”
mentioning
confidence: 99%
“…In this study we use the 5D parameters of stars in Sample II (R.A., Decl., , µ α cos δ, and µ δ ) from Gaia EDR 3. Since only a small fraction of the stars in each cluster have RV measurements, we adopt the higheraccuracy radial velocities from Jackson et al (2020) and Bailey et al (2018) as supplementary data. The RVs of stars in the ten target clusters are obtained from Jackson et al (2020); these are part of the Gaia-ESO Survey (GES, Gilmore et al 2012) with an uncertainty of 0.4 km s −1 , obtained using FLAMES (the Fiber Large Array Multi Element Spectrograph) combined with the GIRAFFE and UVES (Ultraviolet and Visual Echelle Spectrograph) spectrographs mounted on the 8-m UT2-Kueyen telescope of the ESO Very Large Telescope facility.…”
Section: Gaia Edr 3 Data Processing and Analysismentioning
confidence: 99%
“…Since only a small fraction of the stars in each cluster have RV measurements, we adopt the higheraccuracy radial velocities from Jackson et al (2020) and Bailey et al (2018) as supplementary data. The RVs of stars in the ten target clusters are obtained from Jackson et al (2020); these are part of the Gaia-ESO Survey (GES, Gilmore et al 2012) with an uncertainty of 0.4 km s −1 , obtained using FLAMES (the Fiber Large Array Multi Element Spectrograph) combined with the GIRAFFE and UVES (Ultraviolet and Visual Echelle Spectrograph) spectrographs mounted on the 8-m UT2-Kueyen telescope of the ESO Very Large Telescope facility. Bailey et al (2018) obtained RVs of stars in NGC 2422 with M2FS (the Michigan/Magellan Fiber System), a multi-object fibre-fed spectrograph on the Magellan/Clay 6.5-m telescope, with a median uncertainty of 0.08 km s −1 .…”
Section: Gaia Edr 3 Data Processing and Analysismentioning
confidence: 99%